Work Culture, Income and Change Management on Employee Performance at Airnav Indonesia Company - Rhomadoni Surya Kahfi Dewanata; Vera Firdaus; Supardi Supardi (International Journal of Economics Development Research (IJEDR), 2024)
Work Culture, Income and Change Management on Employee Performance at AirNav Indonesia Company. After the spread of the COVID-19 virus, many changes have occurred at the AirNav Indonesia company. Starting from work culture to income when COVID-19 hit which has an impact on the performance of employees in the AirNav Indonesia work environment to date.